Phenolic Plant Extracts Induce Sirt1 Activity and Increase Antioxidant Levels in the Rabbit's Heart and Liver. (4th July 2018) - Corbi, G.; Conti, V.; Komici, K.; Manzo, V.; Filippelli, A.; Palazzo, M.; Vizzari, F.; Davinelli, S.; Di Costanzo, A.; Scapagnini, G.; Ferrara, N.; Casamassima, D.
Abstract : Background . Several dietary phytochemicals potentially regulate the equilibrium between oxidant and antioxidant species. The aim of this study was to evaluate the effects of Lippia citriodora, Raphanus sativus, and Solanum lycopersicum on blood parameters, oxidative/antioxidant status, and SIRT1 activity in the rabbit's heart and liver. Methods . Twenty rabbits were divided into 4 groups of 5 animals each. The control group (CN) received a feed without any additives. One intervention group received a supplement containing verbascoside (VB), another Raphanus sativus extract (RAP), and lastly lycopene (LYC). Oxidant-antioxidant parameters and SIRT1 activity were measured in plasma and in the heart and liver, respectively. Results . The treatment with VB, RAP, and LYC resulted in a marked improvement in the blood lipid and glycaemic profile in respect to CN. VB was the most effective, but all three plant extracts induced a significant reduction in oxidant parameters as well as an increase in antioxidant tissue activity and vitamin A and E levels. SIRT1 activity was significantly increased in both VB and LYC compared to CN, but the increased levels in the VB group were far the highest. The multivariate analysis suggests that the benefits of VB, particularly the antiglycaemic and antioxidant effects, might be mediated by increasing SIRT1 activity.